Course Achievement Evaluation Using Concept Map in Traditional Learning. Issue 5 (October 2020) - Huang, Peihan; Lin, Shaohui; Yuan, Junying; Chen, Haishan
Abstract: Concept map (CM) has been proved to be pretty efficient in learning assessment. Existing CM-based learning assessment methods tend to compare a CM delivered by a student against a standard version or expert version. This manuscript employs CM as a technique to assess students' learning performance from the results of a bunch of traditional performance assessments. The experimental results show a more comprehensive result for interpreting students' learning performance and provide some indications of the gap between teaching and learning for future teaching reforms.